Tuning the Charge Carrier Polarity of Organic Transistors by Varying the Electron Affinity of the Flanked Units in Diketopyrrolopyrrole‐Based Copolymers. (20th December 2019) - Liu, Qian; Wang, Yang; Kohara, Akihiro; Matsumoto, Hidetoshi; Manzhos, Sergei; Feron, Krishna; Bottle, Steven E.; Bell, John; Michinobu, Tsuyoshi; Sonar, Prashant
Abstract: Fine‐tuning of the charge carrier polarity in organic transistors is an important step toward high‐performance organic complementary circuits and related devices. Here, three new semiconducting polymers, namely, pDPF‐DTF2, pDPSe‐DTF2, and pDPPy‐DTF2, are designed and synthesized using furan, selenophene, and pyridine flanking group‐based diketopyrrolopyrrole cores, respectively. Upon evaluating their electrical properties in transistor devices, the best performance has been achieved for pDPSe‐DTF2 with the highest and average hole mobility of 1.51 and 1.22 cm 2 V −1 s −1, respectively. Most intriguingly, a clear charge‐carrier‐polarity change is observed when the devices are measured under vacuum. The pDPF‐DTF2 polymer exhibits a balanced ambipolar performance with the µ h / µ e ratio of 1.9, whereas pDPSe‐DTF2 exhibits p ‐type dominated charge carrier transport properties with the µ h / µ e ratio of 26.7. Such a charge carrier transport change is due to the strong electron‐donating nature of the selenophene. Furthermore, pDPPy‐DTF2 with electron‐withdrawing pyridine flanking units demonstrates unipolar n ‐type charge transport properties with an electron mobility as high as 0.20 cm 2 V −1 s −1 . Overall, this study demonstrates a simple yet effective approach to switch the charge carrier polarity in transistors by varying the electron affinity of flanking groups of the diketopyrrolopyrrole unit. Abstract : Three diketopyrrolopyrrole (DPP) based copolymers are applied in organic transistors. p ‐Type behavior is observed for all the materials in air. However, charge‐carrier‐polarity change occurs by changing the measurement atmosphere and the electron affinity of the flanking groups of the DPP core.